PENDIDIKAN DI ERA DIGITAL - Amin Rais; Aris Munandar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The digital era has brought significant changes to the world of education, both in terms of approaches, methods, and learning media. Education is no longer limited to physical classrooms but has evolved toward flexible, interactive learning that utilizes information and communication technology. This paper discusses the transformation of education in response to the demands of digitalization, including changes in the teacher’s role as a facilitator, the use of technology as a learning medium, and the emergence of new learning models such as blended learning, flipped classrooms, and e-learning. A literature review was used as the data collection method by examining various relevant scientific journals. The analysis shows that technology, particularly Learning Management Systems (LMS), plays a vital role in improving the quality of education through material management, data-based evaluation, and enhanced learning interaction. The use of technology enables learning to become more inclusive, independent, and adaptive to the needs of digital-native learners. In addition, teachers are required to improve their digital competence to design varied and creative learning media. Ultimately, the transformation of education in the digital era not only changes teaching and learning mechanisms but also creates a new paradigm that is more open, collaborative, and technology-based.